Imperfect Competition, Information Heterogeneity, and Financial Contagion - Pasquariello, Paolo (Review of Financial Studies, 2007)
[This study examines how heterogeneity of private information may induce financial contagion. Using a model of multi-asset trading in which the three main channels of contagion through financial linkages in the literature (correlated information, correlated liquidity, and portfolio rebalancing) are ruled out by construction, I show that financial contagion can still be an equilibrium outcome when speculators receive heterogeneous fundamental information. Risk-neutral speculators trade strategically across many assets to mask their information advantage about one asset. Asymmetric sharing of information among them prevents rational market makers from learning about their individual signals and trades with sufficient accuracy. Incorrect cross-inference about terminal payoffs and contagion ensue. When used to analyze the transmission of shocks across countries, my model suggests that the process of generation and disclosure of information in emerging markets may explain their vulnerability to financial contagion.]